Asset and Liability Management in Health Insurance - ILYAS, Ashiq Mohd; RAJASEKARAN, S. (Journal of Advanced Studies in Finance; Vol 8 No 1 (2017): JASF Volume VIII Issue 1(15) Summer 2017DO - 10.14505//jasf.v8.1(15).02, 2017)
In this paper, we focus on the issues in asset and liability management (ALM) in health insurance particularly in the Indian context. The regulations in health insurance imposed by Insurance regulatory and development authority (IRDA) for ALM policies, Stress testing and mandated Investments are reflected in this paper. An analytic approach has been incorporated for measuring duration, convexity, clean price and dirty price with an amendment in yield till maturity for the bond securities in the portfolio of the health insurer. The Changes in the projection of portfolio values with a change in yield have been graphically analysed. The Reddingtons immunisation conditions were used for the portfolio of the insurer to analyse the immunisation level. The basic chain ladder method is incorporated to predict the Incurred But Not Reported (IBNR) claims reserve for best estimations of liability value of the insurer.